Means to an end : marketing research on Icelandic cosmeceutical brands and consumers' motivations for purchase - Stefanía Hrönn Guðrúnardóttir 1988- (2016)
This MSc thesis in international business explores the layout and sudden surge of the newly emerged Icelandic cosmeceutical industry and its consumer’s motivations for their skin care purchases. The research is twofold, study 1 is conducted with semi-structured interviews with marketing and branding managers of some of the most relevant brands in the Icelandic cosmeceutical industry. Study 2 applies the means end chain (MEC) theory to cosmeceutical purchases, and uses the laddering method to interview skin care consumers and explores what motivates them to buy Icelandic skincare brands in particular. A hierarchical value map (HVM) is constructed to display the results from the laddering process and analyzed in combination with the themes and layout of the Icelandic cosmeceutical market with results of study 1. The research shows that Iceland offers ideal conditions and knowledge for a cosmeceutical industry as is emerging and that Icelandic consumers welcome this development, especially in light of various sociological factors that have emerged over the last years. The research also explores a way to move forward for the brands as they are all entering foreign markets, and the research shows that the “Iceland” factor can contribute to success abroad due to nation branding efforts.